Epileptogenic networks in nodular heterotopia: A stereoelectroencephalography study. (6th October 2017) - Pizzo, Francesca; Roehri, Nicolas; Catenoix, Hélène; Medina, Samuel; McGonigal, Aileen; Giusiano, Bernard; Carron, Romain; Scavarda, Didier; Ostrowsky, Karine; Lepine, Anne; Boulogne, Sébastien; Scholly, Julia; et al.
Summary: Objective: Defining the roles of heterotopic and normotopic cortex in the epileptogenic networks in patients with nodular heterotopia is challenging. To elucidate this issue, we compared heterotopic and normotopic cortex using quantitative signal analysis on stereoelectroencephalography (SEEG) recordings. Methods: Clinically relevant biomarkers of epileptogenicity during ictal (epileptogenicity index; EI) and interictal recordings (high‐frequency oscillation and spike) were evaluated in 19 patients undergoing SEEG. These biomarkers were then compared between heterotopic cortex and neocortical regions. Seizures were classified as normotopic, heterotopic, or normoheterotopic according to respective values of quantitative analysis (EI ≥0.3). Results: A total of 1, 246 contacts were analyzed: 259 in heterotopic tissue (heterotopic cortex), 873 in neocortex in the same lobe of the lesion (local neocortex), and 114 in neocortex distant from the lesion (distant neocortex). No significant difference in EI values, high‐frequency oscillations, and spike rate was found comparing local neocortex and heterotopic cortex at a patient level, but local neocortex appears more epileptogenic (p < 0.001) than heterotopic cortex analyzing EI values at a seizure level. According to EI values, seizures were mostly normotopic (48.5%) or normoheterotopic (45.5%); only 6% were purely heterotopic. A good long‐term treatment response was obtained in only two patients after thermocoagulation and surgical disconnection. Significance: This is the first quantitative SEEG study providing insight into the mechanisms generating seizures in nodular heterotopia. We demonstrate that both the heterotopic lesion and particularly the normotopic cortex are involved in the epileptogenic network. This could open new perspectives on multitarget treatments, other than resective surgery, aimed at modifying the epileptic network.